Clinical recommendations on Cardiac-CT in 2015: a position paper of the Working Group on Cardiac-CT and Nuclear Cardiology of the Italian Society of Cardiology. Issue 2 (February 2016) - Andreini, Daniele; Martuscelli, Eugenio; Guaricci, Andrea Igoren; Carrabba, Nazario; Magnoni, Marco; Tedeschi, Carlo; Pelliccia, Antonio; Pontone, Gianluca
Abstract : We worked out a position paper on cardiac-computed tomography (CCT) endorsed by the Working Group on CCT and Nuclear Cardiology of the Italian Society of Cardiology. The CCT clinical indications were discussed and formulated according to the following two modalities: a brief paragraph dedicated to each indication, with the description of clinical usefulness of different indications; and each indication was rated by the technical panel for appropriateness, using a score assessing whether the use of CCT for each indication is appropriate, uncertain, or inappropriate. All conventional CCT clinical indications, regarding coronary and noncoronary evaluation, were discussed and rated. Moreover, we wrote specific sections regarding the newest CCT applications, such as stress perfusion computed tomography, noninvasive evaluation of fractional flow reserve, and CCT use in athletes. The present study has the following two main objectives: because the diagnostic performance of coronary computed tomography angiography (CCTA) is strictly dependent on adequate technology and local expertise, we strove to provide clinical recommendations on CCTA that may help Italian physicians involved with this diagnostic tool; and to give an update on new indications of CCTA, such as its use for safely discharging patients with suspected acute coronary syndromes from the emergency department, and latest clinical results that have been made possible by the remarkable technology developments of the scanners.